Squamous Odontogenic Tumor-Like Proliferation in Odontogenic Cysts: Report of Two Cases - N Mahdavi; S Rahrotaban; A Sedaghati (Islamic Azad University, 2019)
Background: Squamous odontogenic tumor-like proliferation (SOT-LP) is a rare benign lesion in the jaws with the same histological pattern to SOT but with different clinical and radiographic features. It originates from the epithelial cell rests of Malassez. The histological findings could be seen in the wall of some odontogenic cysts. Knowledge about the features of this lesion can help us in the diagnosis, treatment, and follow-up. Case Presentation: Here, we present two cases of SOT-LP in the wall of a radicular cyst and a residual cyst. Conclusion: SOT-LP shares several histologic characteristics with benign and malignant central jaw tumors. Making a definitive diagnosis is crucial to avoid incorrect treatment.